Multiple Extramedullary-Bone Related and/or Extramedullary Extraosseous Are Independent Poor Prognostic Factors in Patients With Newly Diagnosed Multiple Myeloma - He, JingSong; Yue, XiaoYan; He, DongHua; Zhao, Yi; Yang, Yang; Zheng, GaoFeng; Zhang, Enfan; Han, XiaoYan; Wu, WenJun; Yang, Li; Chen, Jing; Cai, Zhen (Frontiers in Oncology, 2021)
Abstract Background: Extramedullary (EM) lesions are common in multiple myeloma (MM) and are often related to the poor prognosis of MM but are scarcely understood. Methods: In this retrospective study, the baseline characteristics of 357 newly diagnosed patients with extramedullary multiple myeloma (EMM) and their impact on the prognosis were analyzed. All patients received first-line treatment with bortezomib-based regimen. Results: The overall incidence rate of EM was 22.4%, and the detection rate of PET/CT was significantly higher than other imaging methods (P=0.015). The cohorts consisted of 10 cases of extramedullary extraosseous (EME) and 70 cases of extramedullary-bone related (EMB), including 53 cases with single site involvement (1 case with EME) and 27 cases with multiple sites (>1 site) involvement (9 cases with EME). EMM patients had high levels of hemoglobin (Hgb, ≥10 g/dL) and serum lactate dehydrogenase (LDH, >245u/L) and are inclined to early-stage revised international staging system (R-ISS). Compared to patients without EM, those with EMM had worse progression-free survival (PFS) (P=0.014) and overall survival (OS) (P=0.032). In addition, patients without EM and those with a single site of EMB had similar PFS and OS, while patients with multiple sites of EMB or EME and multiple sites of EMB with EME had poor PFS and OS. Multivariate analysis confirmed that multiple sites of EMB and/or EME were independent prognostic predictors affecting PFS and OS in newly diagnosed MM patients. Conclusions: This study suggested that among patients treated with bortezomib-based regimens, multiple sites of EMB and/or EME are independent poor prognostic factors for newly diagnosed MM patients, while a single site of EMB does not affect the survival of newly diagnosed MM patients. Thus, these findings could be used as a reference for the study of EMM patients in the new drug era, but prospective clinical studies are needed to provide evidence-based data for the diagnosis and treatment of EMM.